Arduino-Based IoT Soil pH Monitoring System for Automated Horticultural Fertilization - Nuzula, Mukhsin; Salat, Junaidi; Ichsan, Muhammad; Fazira, Zetta; Rahmi, Qairul (PTE FTK UIN Ar-Raniry, 2026)
Precision fertilization is crucial for enhancing nutrient use efficiency and maintaining optimal soil conditions in horticultural crop cultivation. While IoT-based agricultural automation has been extensively researched, most studies focus on soil moisture-based irrigation, whereas the use of soil pH as a real-time control parameter in automated fertilization systems with remote monitoring remains limited. This limitation hinders accurate nutrient management and timely corrective actions in horticultural production. Therefore, this study aims to design and implement an Arduino-based automated fertilization system integrated with soil pH sensors and IoT technology. The proposed system continuously monitors soil acidity levels and automatically regulates liquid fertilizer application based on predefined pH thresholds. Testing results demonstrate that the soil pH sensor effectively measures acidity levels within the 5.32–6.50 pH range. The system successfully activates fertilizer application when pH values ​​fall below the set threshold, delivering a volume of 150–200 mL per 60-second cycle. The findings indicate that integrating pH-based decision-making with IoT-based monitoring has the potential to support precision fertilization in horticultural cultivation